The displacement of oil by aqueous solutions in porous media. - Sakanoko, Mariame. (University of Ottawa (Canada), 2001)
The immiscible displacement of oil by water in a petroleum reservoir has been simulated in the laboratory using a consolidated porous medium constructed out of silica sand particles. Four distinct displacement flow modes were employed, namely horizontal, vertical upward, vertical downward, and transverse. Experiments were carried out by displacing the oil phase (heavy paraffin oil) by the aqueous phase (dyed glycerol solution) at different oil/water viscosity ratios, at different flow rates, and in the presence and absence of connate water (connate water is the name given to the very small amount of water that occurs naturally in petroleum reservoirs). The objective of this study was to investigate the effects of viscosity ratio, flow rate, and flow mode on the oil recovery efficiency. In the absence of connate water, a decrease in the oil recovery is observed when the oil/water viscosity ratio increases for all four flow modes but the displacement patterns are different for each flow mode. In the presence of connate water, the dependence of oil recovery on viscosity ratio is similar although in this case the displacement patterns are almost indistinguishable for the four different flow modes on account of coalescence of the connate water phase with the displacing aqueous phase. Without connate water, the highest recovery is obtained in the vertical upward mode where the buoyancy forces stabilize the displacement process. Conversely, in the vertical downward flow mode, the instability promoted by gravity leads to a low recovery. Comparison of the results obtained with and without connate water shows that connate water has a negative effect on the recovery and, moreover, that the synergistic effect between the viscosity ratio and the connate water reduces the oil recovery efficiency significantly.
Keywords: Engineering, Petroleum.